Camera Palaestina : Photography and Displaced Histories of Palestine. - Nassar, Issam; Sheehi, Stephen; Tamari, Salim (Berkeley : University of California Press, 2022)
A free open access ebook is available upon publication. Learn more at www.luminosoa.org. Camera Palaestina is a critical exploration of Jerusalemite chronicler Wasif Jawhariyyeh (1904-1972) and his seven photography albums entitled The Illustrated History of Palestine. Jawhariyyeh's nine hundred images narrate the rich cultural and political milieu of Ottoman and Mandate Palestine. Nassar, Sheehi, and Tamari locate this archive at the juncture between the history of photography in the Arab world and the social history of Palestine. Shedding new light on this foundational period, the authors explore not just major historical events and the development of an urban bourgeois lifestyle but a social field of vision of Palestinian life as exemplified in the Jerusalem community. Tracking the interplay between photographic images, the authors offer evidence of the unbroken field of material, historical, and collective experience from the living past to the living present of Arab Palestine.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books